2005
DOI: 10.1161/01.str.0000153015.57892.66
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine for Safe and Extended Use of Thrombolysis in Stroke

Abstract: on behalf of the TEMPiS GroupBackground and Purpose-Systemic thrombolysis represents the only proven therapy for acute ischemic stroke, but safe treatment is reported only in established stroke units. One major goal of the ongoing Telemedic Pilot Project for Integrative Stroke Care (TEMPiS) in Bavaria is to extend the use of tissue plasminogen activator (tPA) treatment in nonurban areas through telemedic support. Methods-The stroke centers in Munich-Harlaching and in Regensburg established a telestroke network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(98 citation statements)
references
References 31 publications
6
89
1
1
Order By: Relevance
“…This is comparable with overseas trials, including the Telemedic Pilot Project for Integrative Stroke Care (TEMPiS) study, which delivered a thrombolysis rate of 2.1% of all stroke patients in its first year of operation, although that trial used a 3-h time window. 16 In addition to introducing thrombolysis, we also aimed to improve the efficiency of stroke management by enhancing the rapidity of assessment and decisionmaking. Door-to-CT time was the variable measured to reflect this efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is comparable with overseas trials, including the Telemedic Pilot Project for Integrative Stroke Care (TEMPiS) study, which delivered a thrombolysis rate of 2.1% of all stroke patients in its first year of operation, although that trial used a 3-h time window. 16 In addition to introducing thrombolysis, we also aimed to improve the efficiency of stroke management by enhancing the rapidity of assessment and decisionmaking. Door-to-CT time was the variable measured to reflect this efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…21 This is despite the proven safety of Telestroke thrombolysis in multiple randomised controlled trials. 16,22 Our study addressed these concerns by measuring the rate of symptomatic intracerebral haemorrhage, a standard safety measure used in thrombolysis trials. Comfortingly, no thrombolysed patients developed symptomatic intracerebral haemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…53 Síðari rannsóknir sýndu fram á að haegt vaeri að baeta verkferla t-PA-gjafar með því að koma á laggir fjarlaekningum. Þessi nálgun á við um ákvörðunartöku t-PA-meðferðar, 54 útilokun einkenna sem líkjast slagi, 55 að tryggja rétt tímamörk, 56 túlkun myndrannsókna 57 auk þess að baeta greiningu og verkferla blóðþurrðarslaga. Gjöf t-PA jókst marktaekt eftir að fjarlaekningum var komið á án aukningar á rangri ákvarðanatöku.…”
Section: Y F I R L I T S G R E I N L Aeknablaðið 2018/104 23unclassified
“…Telemedicine provides an opportunity to optimize acute stroke treatment regardless of the geographical location. A large telemedicine based study has shown comparable safety and efficacy results in acute stroke patients treated with intravenous tPA via telemedicine conference using video and audio linkage 7 . Their findings suggested that physicians with little experience in treating acute stroke with thrombolytic agent, when guided remotely via telemedicine by stroke experts, could achieve comparable results to tertiary centres 7 .…”
Section: Original Articlementioning
confidence: 99%
“…A large telemedicine based study has shown comparable safety and efficacy results in acute stroke patients treated with intravenous tPA via telemedicine conference using video and audio linkage 7 . Their findings suggested that physicians with little experience in treating acute stroke with thrombolytic agent, when guided remotely via telemedicine by stroke experts, could achieve comparable results to tertiary centres 7 . A recent randomized control study comparing videoconferencing with computed tomography (CT) image review to telephone consultations without CT image review showed similar outcome at 90 days 8 .…”
Section: Original Articlementioning
confidence: 99%